Fenomena Cashless Society Di Era Milenial Dalam Perspektif Islam - Sifwatir Rif’ah (Al-Musthofa: Journal of Sharia Economics, 2019)
This article aims to examine the transformation of money as a means of modern financial payment. In the viewpoint of finance, electronic money is considered sufficient as a requirement of an object that can be functioned into money because it is easily to be stored, carried and not damaged traightforwardly. Indonesian Bank itself continues to encourage the use of electronic non-cash transactions. Several companies especially banking sectors apply electronic money in order to improve the convenience of the electronic money customers. Bank Indonesia also continuously strives to develop the system and rules on electronic financial transactions. Thus, it is expected that public society select electronic money transactions as a tool of payment for the advancement of the global economy in the millenial age.